A Discussion of Péter Krasztev and Jon Van Til's The Hungarian Patient: Social Opposition to an Illiberal Democracy. Issue 2 (8th June 2017) - Fodor, Eva
Abstract : In the wake of the Revolutions of 1989, Hungary was long considered one of the "success stories" of post-communist transition to liberal democracy. Yet in recent years the Hungarian government, under the leadership of Prime Minister Viktor Orban, has pioneered a new conception of "illiberal democracy." In a July 2014 speech, Orban indeed declared that "the era of liberal democracies is over." Similar declarations can be heard in other parts of post-communist Eastern Europe. The Hungarian Patient: Social Opposition to an Illiberal Democracy, is a collection of essays by Hungarian social scientists and intellectuals reflecting on both the sources of this emergent illiberalism and the sources of opposition to it. Because it is important for American political scientists to understand the way their colleagues in other parts of the world reflect on the challenges of democracy, and because the Hungarian situation is significant for the future of Europe and the EU, we have invited a wide range of scholars to comment on the book and on its topic—the significance of the emergence of "illiberal democracy" in Hungary and in Europe.